Strategi Pendampingan Orang Tua terhadap Intensitas Penggunaan Gadget pada Anak - Nurul Novitasari (Universitas Al-Hikmah Indonesia, 2019)
Generally children spend time playing and trying new things. Not infrequently they play and satisfy their curiosity through gadgets, because gadgets are an interesting tool, children should still spend more time playing with peers. The development of gadgets is very influential in the development of human life. This phenomenon is most easily found in children who come from families where gadgets are no longer a luxury item for them. So parents have to control children who use gadgets. There are certain hours a child holds a cellphone, there are certain hours a child with parents. One negative impact of the use of gadgets on children include: 1) being private closed, 2) impaired brain health, 3) impaired eye health, 4) impaired hand health, 5) sleep disturbances, 6) aloofness, 7) violent behavior, 8) fading creativity, 9) radiation exposure, and 10) cyberbullying threats. The most influential figure in preventing or overcoming the negative effects of gadgets are parents. So parents have a big role in guiding and preventing gadget technology from having a negative impact on children. Ways that must be done by parents are as follows: 1) select according to the age of the child, 2) Be selective in choosing the game application in the gadget, 3) Accompany children in playing, 4) Limit the time playing gadget for children, and 5) Invite children to do positive activities.